Evaluation of the single-dose pharmacokinetics and pharmacodynamics of apixaban in healthy Japanese and Caucasian subjects - Frost C; Shenker A; Jhee S; Yu Z; Wang J; Bragat A; Pursley J; LaCreta F (Dove Medical Press, 2018)
Charles Frost,1 Andrew Shenker,1 Stanford Jhee,2 Zhigang Yu,1 Jessie Wang,3 Alexander Bragat,1 Janice Pursley,4 Frank LaCreta1 1Exploratory Clinical and Translational Research, Bristol-Myers Squibb, Princeton, NJ, USA; 2PAREXEL International Early Phase, Glendale, CA, USA; 3Exploratory Development Global Biometric Sciences, Bristol-Myers Squibb, Princeton, NJ, USA; 4Analytical and Bioanalytical Development, Bristol Myers Squibb, Princeton, NJ, USA Purpose: This double-blind, placebo-controlled, intra-subject, dose-escalation study assessed single-dose safety, pharmacokinetics, and pharmacodynamics of apixaban in healthy Japanese and Caucasian subjects. Subjects and methods: Sixteen healthy male Japanese and sixteen healthy male Caucasian subjects, matched for age, weight, and smoking status were randomized to receive four sequential single oral doses of either apixaban (2.5, 10, 25, and 50 mg) or matched placebo. Doses were separated by a ≥5-day washout. Blood samples were collected for the determination of apixaban plasma concentration, clotting times (international normalized ratio [INR], activated partial thromboplastin time, and modified prothrombin time [mPT]), and ex vivo thrombin generation (TG). Urine samples were collected for the analysis of apixaban concentration. Results: Ascending single doses of apixaban 2.5–50 mg were safe and well tolerated by all subjects. Apixaban exposure increased the dose proportionally up to 10 mg. Apixaban reached maximum concentrations (Cmax) 3–4 h postdose, with mean Cmax ranging from 52.5–485.0 to 44.8–494.3 ng/mL in Japanese and Caucasian subjects. The mean half-life was ~8 and ~13 h and the renal clearance was 1.1 and 0.8 L/h in Japanese and Caucasian subjects, respectively. Pharmacodynamic assessments were similar between ethnic groups, with comparable dose-related prolongation of INR and mPT and inhibition of TG. Conclusion: Ascending single doses of apixaban over a 20-fold dose range were safe and well tolerated in Japanese and Caucasian subjects in this study. The consistency between pharmacokinetic and pharmacodynamic measures in Japanese and Caucasian subjects indicates that apixaban may be administered as a fixed dose with no need for adjustment in Japanese patients. Keywords: safety, pharmacokinetics, pharmacodynamics, Japanese, apixaban, anticoagulation, Asian, novel, Eliquis